Parametric analysis of a semi-closed-loop linear joule engine generator using argon and oxy-hydrogen combustion. (15th February 2021) - Ngwaka, Ugochukwu; Wu, Dawei; Happian-Smith, Julian; Jia, Boru; Smallbone, Andrew; Diyoke, Chidiebere; Roskilly, Anthony Paul
Abstract: The paper introduces a novel semi-closed-loop Linear Joule Engine Generator (LJEG) using argon as the major working fluid and oxy-hydrogen combustion for heat addition. The linear compressor and expander in the LJEG apply double-acting piston configuration to maximise power density, and an oxy-hydrogen-argon reactor has ultra-high heat transfer efficiency and emits ultimate zero carbon, NOx, and particulate emissions. The proposed LJEG is developed from a previous lab-scale LJEG prototype using air as the working fluid. A comparison study demonstrates the advantages of the new conceptual design; substituting air with argon as the major working fluid resulted in increased system speed, decreased indicated power, and over 60% indicated efficiency improvement. A further parametric analysis was conducted using a validated model to reveal the influence of different intake and exhaust valve timing, compressor/expander diameter ratio, electric load, and operating temperature. The analysis shows that the system efficiency decreases with the extended intake duration, but it could be improved with the extension of expander exhaust duration. Power output increases with longer expander intake duration, however, its relationship with diameter ratio of compressor and expander is dependent on adopted expander exhaust valve timing, a peak power output of 4.7 kW could be achieved at expander intake temperature of 1073 K. System operating temperature for the optimal performance is also highly dependent on valve timings. Piston stroke length is adversely affected by an increase in compressor/expander diameter ratio and operating temperature. Peak system efficiencies of 40% and 60% could be achieved when the compressor/expander diameter ratio is 0.70 and 0.93, respectively. Highlights: Performance of a semi-closed-loop Linear Joule Engine Generator was investigated. Use of argon as the major working fluid is proposed in argon-oxy-hydrogen combustion. The engine realises the zero-carbon potential of hydrogen with no NOx emissions. Parametric analysis of the geometric and operational variables was conducted.